Diterpenoid alkaloids with chemotaxonomic significance from Aconitum spathulatum. (August 2020) - Shen, Xiaojing; Yin, Tianpeng; Li, Xingyu; Ma, Junrong; Lv, Qi; Zhang, Ganjuan
Abstract: Diterpenoid alkaloids have been acknowledged as of chemotaxonomic significance in plants from the genus Aconitum (Ranunculaceae). Phytochemical investigation on the Aconitum spathulatum W. T. Wang, an endemic Aconitum species in China, has led to the isolation of twelve C19 -diterpenoid alkaloids. The chemotaxonomic significance of these compounds are summarized. Highlights: Eleven C19 -diterpenoid alkaloids were isolated from Aconitum spathulatum for the first time. The chemotaxonomic significance of the isolated alkaloids was summarized. The distribution and chemotaxonomic significance of yunaconitine in Aconitum genus was summarized for the first time.